Searching for Virtue: Physiognomy, Sociability, and Taste in Isabella Teotochi Albrizzi's "Ritratti" - Dalton, Susan (Eighteenth-Century Studies, 2006)
One of the most famous Venetian women of her time, Isabella Teotochi Albrizzi (1760-1836) was known not only for her salon, but also for her published works. One of these pieces, Teotochi Albrizzi's Ritratti (1807), a series of literary portraits, reveals Europe's concern over the simulation of virtue in a society beginning to judge merit by behavior and self-presentation rather than birth. Teotochi Albrizzi's portraits demonstrate the strategies used to discern character and how the author drew on ideas concerning sexual difference in the realm of aesthetics to address concerns raised by shifting practices of sociability.